Chemical and flavour changes in jackfruit (Artocarpus heterophyllus Lam.) cultivar J3 during ripening - Ong, B. T.; Sheikh Abdul Hamid, Nazimah; Osman, Azizah; Quek, Siew Young; Voon, Yit Yang; Mat Hashim, Dzulkifly (Elsevier, 2006)
Chemical composition (titratable acidity, moisture content, crude fibre, colour, pH, soluble solids, sugars, organic acids) and flavour changes during ripening of jackfruit (Artocarpus heterophyllus L.) cultivar J3 were evaluated. Significant (p < 0.05) changes in titratable acidity and colour was obtained, but no significant changes were found in moisture and crude fiber contents during ripening. Total soluble solids and total sugars increased significantly (p < 0.05) throughout the ripening process. Total soluble solids at the top portion of the fruit were significantly (p < 0.05) higher than middle and bottom portions of the same fruit. A high content of malic acid was found in unripe fruit (day 1). In contrast, ripened fruit (days 5 and 6) contained a high amount of citric acid. Overall, the total amount of organic acids was found to decrease from the early to later stage of ripening. A total of 23 volatile compounds were tentatively identified by GC and GC–MS. The number of peaks was observed to increase throughout the ripening process. In this study, data obtained suggest that the ripening process of jackfruit was at its optimum at day 5 after harvest.